Neml sûresinin kırâatlar bağlamında incelenmesi ve manaya etkisi - Akdağ, İsa (My University, 2022)
Hz. Peygamber, Allah’ın oku emrine muhatap olarak Cebrail aracılığıyla Kur’an-ı Kerim’i öğrenmiş ve usûlüne uygun bir şekilde tilâvet ederek bu konuda ashâbını eğitmiştir. Kırâat ilmi, Kur’ân-ı Kerîm’in nüzûlü ile başlayarak Hz. Peygamber’in, ashâbına, onların da daha sonra gelecek tâbiîn devrine aktarımlarıyla devam etmiştir. Hicrî ikinci asrın sonlarından itibaren kırâat ekollerinin kurulmasıyla birlikte kırâat sahasında güvenilir imamların okuyup öğrenmeleri ve bunları yazılı olarak aktarmalarıyla kırâatler doğru bir şekilde günümüze kadar gelebilmiştir. Bu çalışmada Neml sûresindeki kıraat farklılıklarının manaya nasıl bir etkide bulunduğu incelenmiştir. Bu çalışmada genel itibari ile sahîh olarak kabul gören kırâatlar tercih edilmiş, sahîh olmayan kırâatlar üzerinde ise durulmamıştır. Neml sûresi temel olarak Allah’ın birliği, Peygamber kıssaları, ahiret hayatı, tekrar diriliş, mahşer, Hz. Süleyman’ın hükümdarlığı ve Sebe’ melikesinin öyküsü gibi konuları içermektedir. Bu sûrenin, konularına ve içeriğine daha iyi anlam verilebilmesi ve manasının bütünüyle ele alınmasına yardımcı olması açısından kırâat farklılıklarının incelenmesi önem arz etmektedir. Bu çalışma da böyle bir düşüncenin eseri olarak ele alınmıştır.

The Prophet (pbuh) was trained to read the Qur'an correctly and beautifully through Gabriel, and he gave this education to his Companions in the best way by various methods. The science of recitation, which started with the revelation of the Qur'an, continued with the companions and began to be recorded in the period of the Tabiun (the generation after the companions). That the recitation schools were established at the end of the second century of the Hijri calendar and that this discipline was obtained and instructed by the reliable masters of these schools together with that it was recorded and transmitted, was important in terms of transmitting the recitations from generation to generation in a correct way. In our study, we will try to explain how the verses of Surah Al-Naml and even the words affects the meaning in the context of the recitations. In general, the recitations that are accepted as authentic will be preferred, and non-authentic recitations will not be overemphasized. Surah Al-Naml basically contains the subjects of the unity of Allah, stories about some Prophets, the life in the Hereafter, the resurrection, the Judgment Day, the reign of Prophet Solomon, and the Queen of Sheba. It is important to examine the recitation differences to give a better meaning to the subjects and content of Surat Al-Naml and to help it be understood holistically.
Keywords: Differences; Farklılıklar; Islam; İslam; Kırâatlar; Kur’ân; Mana; Meaning; Neml Sûresi (Karınca) Quran; Recitations; Surah An-Naml (The Ant)